Tailoring magnesium-doped coatings for improving surface and biological properties of titanium-based dental implants - Dini, Caroline (2025)
Physicochemical modifications of biomaterials have been proposed to overcome bone integration impairment and microbial infections. The magnesium (Mg) incorporation on dental implant surfaces has shown positive results in bone-to-implant contact and in the reduction of microbial colonization. Here, we explored the potential of using different Mg precursors to synthesize coatings via plasma electrolytic oxidation (PEO) on commercially pure titanium (cpTi), aiming to optimize the surface and biological properties. For this, we investigated Mg acetate and Mg nitrate precursors in different concentrations (0.04 M and 0.12 M), using calcium (Ca) and phosphorus (P) as the base electrolyte for all groups. Coatings with only the CaP base electrolyte were used as the control group. The surfaces were characterized by confocal laser scanning microscopy, scanning electron microscopy, film thickness measurement, profilometry, wettability, X-ray diffraction, energy dispersive spectroscopy, X-ray photoelectron spectroscopy, electrochemical behavior, and ion release. For biological analyses, the adhesion (2 h) of Streptococcus sanguinis was evaluated, as well as MC3T3-E1 osteoblastic cells proliferation at 1 and 3 days, and mineralization of calcium phosphates after 28 days. PEO treatment using different Mg precursors promoted physicochemical modifications of cpTi. The experimental groups MgN 0.04 and MgN 0.12 exhibited higher surface roughness and wettability compared to the other surfaces. Regardless of the Mg precursor, the higher the ion concentration in the electrolyte solution, the higher the Mg atomic concentration on the surfaces. Concerning the electrochemical behavior, the results indicated that the incorporation of Mg in the coatings may enhance the electrochemical performance. Mg treated surfaces did not promote greater bacterial adherence when compared to the control. MgAc 0.04 and MgAc 0.12 coatings displayed improved MC3T3-E1 pre-osteoblastic cells proliferation at day 3 compared to other groups. The hydroxyapatite formation on MgAc 0.12 surfaces was higher than in the other groups. Our data indicate that Mg precursor selection positively influences physicochemical and biological properties of coatings. Specifically, MgAc 0.12 surfaces showed the most promising surface features with greater cell proliferation, without affecting microbial colonization, being an excellent candidate for surface treatment of titanium-based dental implants.